2014
DOI: 10.1542/hpeds.2014-0020
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Long Length of Stay in Infants Hospitalized With Urinary Tract Infection

Abstract: OBJECTIVE: Urinary tract infection (UTI) is the most common serious bacterial infection in infants. To use resources optimally, factors contributing to costs through length of stay (LOS) must be identifi ed. This study sought to identify clinical and health system factors associated with long LOS in infants with UTI. METHODS:Using a case-control design, we included infants <6 months old hospitalized with UTI. Cases had LOS ≥96 hours; controls had LOS <96 hours. Clinical and health system variables were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…31 Nonetheless, relatively few empirical data exist regarding predictors of LOS for young infants admitted for nonsurgical conditions. Others have reported that prematurity and concomitant comorbidities were associated with prolonged LOS for infants ,6 months of age with UTI, 32 and the specific infecting pathogen was associated with an increased LOS in children ,2 years of age with bronchiolitis. 33 We are not aware of any such study of infants and LOS, for any medical condition, performed on a large longitudinal data set such as we report here.…”
Section: Discussionmentioning
confidence: 95%
“…31 Nonetheless, relatively few empirical data exist regarding predictors of LOS for young infants admitted for nonsurgical conditions. Others have reported that prematurity and concomitant comorbidities were associated with prolonged LOS for infants ,6 months of age with UTI, 32 and the specific infecting pathogen was associated with an increased LOS in children ,2 years of age with bronchiolitis. 33 We are not aware of any such study of infants and LOS, for any medical condition, performed on a large longitudinal data set such as we report here.…”
Section: Discussionmentioning
confidence: 95%
“…No serious complications were observed among 257 non-bacteraemic infants treated for <48 hours with intravenous antibiotics, and the overall risk of treatment failure was low (0.4%). All infants who experienced treatment failure had a risk factor such as prematurity, CAKUT or antibiotic resistance 31. Infants treated for <48 hours were predominantly female, aged >30 days, term, afebrile, with a CRP <20 mg/L and no CSF pleocytosis.…”
Section: Discussionmentioning
confidence: 99%